Development of Learning Media "Environmental Pollution" with Methods Guided Discovery at the Environmental Health Study Program UNISLA - Mimatun Nasihah; Rizky Rahadian Wicaksono (Jurnal EnviScience (Environment Science), 2018)
So far, in the Environmental Health Study Program of Lamongan Islamic University, the existence of learning device is not complete yet, especially in Environmental Pollution learning. On that basis of do this research is aimed at developing learning tools that are oriented in the model of learning  device  development  according  to  Kemp  and  improve  student  learning  outcomes  with guided discovery method. Subject of research 10 students of Environmental Health Studies Program of Lamongan Islamic University, with one group pretest-posttest design. Validation results indicate that learning tools are feasible to use, learning management can be well implemented, developed instruments  have  reliability  more  than  75%.  The  result  of  data  analysis  shows  that  the  lecturer's most  prominent  activity  is  to  guide  the  students  in  carrying  out  the  discovery  activities.  Student response to learning method of guided discovery good and interested (95%), learning result at pre test of 20 and posttest equal to 92. It was concluded that the learning tools developed were feasible to  be  used  with  guided  discovery  learning  methods  in  environmental  pollution  causes  and  able improved student learning outcomes